Description of bilateral ideals in a class of noncommutative rings. II - Bavula, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
For generalized Weyl algebras containing the universal enveloping algebra $U_{sl} (2, К)$ of the Lie algebra $sl (2)$ over a field with characteristic zero, bilateral ideals are classified. We show that a product of ideals is commutative and any proper ideal can be uniquely decomposed into a product of primary ideals.